Characteristics and analysis of static strain response on typical asphalt pavement using fiber Bragg grating sensing technology - Liu, Hongfu; Chen, Bo; Cao, Zhonglu; Pan, Qinxue; Huang, Tuo; Lv, Songtao; Qian, Guoping (Frontiers in Built Environment, 2024)
Numerically, the peak strain of asphalt surface course is larger than that of base course. The peak strain of semi-rigid base asphalt pavement appears at the bottom of upper surface course while the peak strain of combined base asphalt pavement occurs at the bottom of the middle, and flexible base asphalt pavement occurs at the bottom of the lower surface course. The peak strain of base course all exists lower base course. The most unfavorable loading position of the base course occurs at the wheel gap of the lower base course. The most adverse loading position of the surface course appears at the wheel load at the bottom of the upper or middle course. The research results can provide data support for improving the design method of asphalt pavement.